2022
DOI: 10.7554/elife.83840
|View full text |Cite
|
Sign up to set email alerts
|

A coordinated transcriptional switching network mediates antigenic variation of human malaria parasites

Abstract: Malaria parasites avoid immune clearance through their ability to systematically alter antigens exposed on the surface of infected red blood cells. This is accomplished by tightly regulated transcriptional control of individual members of a large, multicopy gene family called var and is the key to both the virulence and chronic nature of malaria infections. Expression of var genes is mutually exclusive and controlled epigenetically, however how large populations of parasites coordinate var gene switching to av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 83 publications
5
18
2
Order By: Relevance
“…Switching to var2csa has been shown to be favourable and is suggested to be the default var gene of choice upon perturbation to var specific heterochromatin (Ukaegbu et al ., 2015). These studies also suggested var2csa has a unique role in var gene switching and our results are consistent with the role of var2csa as the dominant ‘sink node’ (Zhang et al ., 2022, Ukaegbu et al ., 2015, Ukaegbu et al ., 2014, Mok et al ., 2008). A previous study suggested in vitro cultivation of controlled human malaria infection samples resulted in dramatic changes in var gene expression (Lavstsen et al ., 2005, Peters et al ., 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Switching to var2csa has been shown to be favourable and is suggested to be the default var gene of choice upon perturbation to var specific heterochromatin (Ukaegbu et al ., 2015). These studies also suggested var2csa has a unique role in var gene switching and our results are consistent with the role of var2csa as the dominant ‘sink node’ (Zhang et al ., 2022, Ukaegbu et al ., 2015, Ukaegbu et al ., 2014, Mok et al ., 2008). A previous study suggested in vitro cultivation of controlled human malaria infection samples resulted in dramatic changes in var gene expression (Lavstsen et al ., 2005, Peters et al ., 2007).…”
Section: Discussionsupporting
confidence: 92%
“…These included var2csa , which had increased expression from generation 1 to generation 2. It has previously been suggested that long-term cultured parasites converge to expressing var2csa , but our findings suggest this begins within two cycles of cultivation (Zhang et al ., 2022, Mok et al ., 2008). Switching to var2csa has been shown to be favourable and is suggested to be the default var gene of choice upon perturbation to var specific heterochromatin (Ukaegbu et al ., 2015).…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, our single cell analysis of var gene expression in the PfSAMS knockdown lines detected activation of a specific subset of var genes, consistent with the hypothesis that certain var genes are more prone to activation than others. This is similar to our previous observations that var activation is biased toward certain subsets of var genes and that this bias shifts overtime, potentially shaping the trajectory of var gene expression over the course of an infection (34). What characteristics determine the likelihood of any particular gene becoming activated remain unknown, although methylation appears to be key to limiting the number of active genes.…”
Section: Discussionsupporting
confidence: 91%
“…The well-accepted, standard paradigm regarding malaria antigenic variation assumes that at any given time, individual parasites express one and only one member of the var gene family. In recent work from our laboratory, we generated an extensive collection of closely related, isogenic 3D7 and NF54 subclones through limiting dilution, thereby enabling us to examine recently cloned parasite populations expressing alternative var genes (34). To our surprise, not all the clones displayed the predicted pattern of single var gene expression.…”
Section: Clonal Parasite Populations From Different Genetic Backgroun...mentioning
confidence: 99%
See 1 more Smart Citation